Предмет: Алгебра,
автор: Denis12sk
x^2-2x+1=6x^2+x-1 Решите уравнение
Ответы
Автор ответа:
0
x²-2x+1-6x²-x+1=0
-5x²-3x+2=0
D=9-4*(-5)*2=9+40=49
x1=(3+7)/-10=-1 x2=(3-7)/-10=0.4
Выбираем лучшее решение!
Автор ответа:
0
x^2-2x+1=6x^2+x-1
-5x^2-2x+1-x+1=0
-5x^2-3x+2=0
D=(-3)^2-4*(-5)*2=9+40=49
x1=(7-(-3))/(2*(-5))=-10/10=-1
x2=(-7-(-3))/(2*(-5))=0.4
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: shopanaruzhan723
Предмет: Физика,
автор: almedinamukasheva
Предмет: Математика,
автор: irinikit666
Предмет: Алгебра,
автор: ramisxay